Magnitude‐dependent and inversely‐related osteogenic/chondrogenic differentiation of human mesenchymal stem cells under dynamic compressive strain. (11th April 2017) - Horner, Christopher B.; Hirota, Koji; Liu, Junze; Maldonado, Maricela; Hyle Park, B.; Nam, Jin
Abstract: Biomechanical forces have been shown to significantly affect tissue development, morphogenesis, pathogenesis and healing, especially in orthopaedic tissues. Such biological processes are critically related to the differentiation of human mesenchymal stem cells (hMSCs). However, the mechanistic details regarding how mechanical forces direct MSC differentiation and subsequent tissue formation are still elusive. Electrospun three‐dimensional scaffolds were used to culture and subject hMSCs to various magnitudes of dynamic compressive strains at 5, 10, 15 or 20% (ε = 0.05, 0.10, 0.15, 0.20) at a frequency of 1 Hz for 2 h daily for up to 28 days in osteogenic media. Gene expression of chondrogenic markers ( ACAN, COL2A1, SOX9 ) and glycosaminoglycan (GAG) synthesis were upregulated in response to the increased magnitudes of compressive strain, whereas osteogenic markers ( COL1A1, SPARC, RUNX2 ) and calcium deposition had noticeable decreases by compressive loading in a magnitude‐dependent manner. Dynamic mechanical analysis showed enhanced viscoelastic modulus with respect to the increased dynamic strain peaking at 15%, which coincides with the maximal GAG synthesis. Furthermore, polarization‐sensitive optical coherence tomography revealed that mechanical loading enhanced the alignment of extracellular matrix to the greatest level by 15% strain as well. Overall, we show that the degree of differentiation of hMSCs towards osteogenic or chondrogenic lineage is inversely related, and it depends on the magnitude of dynamic compressive strain. These results demonstrate that multiphenotypic differentiation of hMSCs can be controlled by varying the strain regimens, providing a novel strategy to modulate differentiation specification and tissue morphogenesis. Copyright © 2016 John Wiley & Sons, Ltd.